Is the so contemned reserpine back? - David García Barreto; Alberto Toruncha Chukram (ECIMED, 2014)
A review of the recent clinical assays that used reserpine at doses of 0.25 mg/day or less was made so as to determine whether these doses may be efficient and well tolerated. The causes leading to a decrease of its prescription, despite having considerably reduced the complications resulting from arterial hypertension, are analyzed. In a cost analysis made it proved to be the cheapest compared with other antihypertensive drugs. It is concluded that the efficiency, good tolerance, duration of the action and low cost of doses under 0.25 mg make it to be considered as a first choice drug in the treatment of primary arterial hypertension. It may be administered alone or combined with low doses of thiazide diuretics.